Third party security audit procedure for network environment - Bin Baharin K.N.; Din N.Md.; Jamaludin Md.Z.; Tahir N.Md. (Institute of Electrical and Electronics Engineers Inc., 2023)
Defending one's systems and networks is an arduous task since computing systems are vulnerable to unauthorized access. Most organizations and companies rely totally on firewalls for network security. Support of firewall installations requires a firewall and network environment audit that is governed by the organization's security policy. The paper describes a security audit procedure based on network posture vulnerabilities. The scope of the work covers some discussion on network perimeter defence and suggestions for the audit procedure. 2003 IEEE.